The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12958-019-0521-8
|View full text |Cite
|
Sign up to set email alerts
|

C-kit signaling promotes human pre-implantation 3PN embryonic development and blastocyst formation

Abstract: Background Although in vitro culture system has been optimized in the past few decades, the problem of few or no high quality embryos has been still not completely solved. Accordingly, fully understanding the regulatory mechanism of pre-implantation embryonic development would be beneficial to further optimize the in vitro embryo culture system. Recent studies have found the expression of c-kit in mouse embryo and its promotion effects on mouse embryonic development. However, it is unclear the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…[25] They observed a positive correlation between SCF expression levels in FF and serum and MII oocyte proportion, which was consistent with the results of our study. We also observed that the number of high-quality embryos, proportion of highquality embryos, and SCF mRNA concentration were significantly higher in the clinical pregnancy group than in the nonclinical pregnancy group, which was consistent with the findings of Tan et al [10] In IF analysis, SCF protein expression levels were higher in the clinical pregnancy group than in the Based on the results of qPCR and IF, it can be concluded that SCF concentration may be an influencing factor in the clinical pregnancy group and pregnancy outcome. We constructed a ROC curve of SCF in GCs combined with serum AMH and found that SCF alone had a good effect on predicting oocyte maturity and clinical pregnancy, although serum AMH is the currently recognized evaluation index.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…[25] They observed a positive correlation between SCF expression levels in FF and serum and MII oocyte proportion, which was consistent with the results of our study. We also observed that the number of high-quality embryos, proportion of highquality embryos, and SCF mRNA concentration were significantly higher in the clinical pregnancy group than in the nonclinical pregnancy group, which was consistent with the findings of Tan et al [10] In IF analysis, SCF protein expression levels were higher in the clinical pregnancy group than in the Based on the results of qPCR and IF, it can be concluded that SCF concentration may be an influencing factor in the clinical pregnancy group and pregnancy outcome. We constructed a ROC curve of SCF in GCs combined with serum AMH and found that SCF alone had a good effect on predicting oocyte maturity and clinical pregnancy, although serum AMH is the currently recognized evaluation index.…”
Section: Discussionsupporting
confidence: 92%
“…Ligand-receptor interactions establish communication between oocytes and GCs, participate in the development and growth of primordial follicles and the appearance of preovulatory dominant follicles, [1,9] and play an important role in early embryonic development and blastocyst formation. [10,11] Mouse and rat ovaries have been used to detect the expression of phosphoinositide 3 kinase/serine-threonine protein XW, LZ, DN, and, AX contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The embryo assessment criteria were executed as the previously described [ 18 ]. A good quality embryo should consist of 7–9 blastomeres with a uniform size, and the fragment proportion should be less than 20% at day 3 for human 2PN embryos after fertilization.…”
Section: Methodsmentioning
confidence: 99%
“…Activated c-kit receptor was associated with multiple kinds of biological events, including proliferation, differentiation, migration and apoptosis, in many types of cells [ 16 , 17 ]. Our previous study reported the expression of c-kit receptor on human embryo and demonstrated that added exogenous SCF to activate c-kit receptor significantly promoted embryo development [ 18 ]. Recently, we found the expression of c-kit receptor on human endometrial stromal cells (ESCs).…”
Section: Introductionmentioning
confidence: 99%